1997
DOI: 10.2116/analsci.13.287
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Aluminum at Trace Level in Water Samples by Visible Absorption Spectroscopy with a Laser Diode

Abstract: KeywordsVisible-laser diode spectrometer, aluminum, water sample , Eriochrome Cyanine R, cetylpyridinium chlorideVarious studies on visible (VIS-LD) and near infrared laser diodes (NIR-LD) have shown their advantage as light sources for several spectrometers.'-4 Visible and near infrared laser diodes have superior great advantages over the conventional sources. They have relatively large output power, narrow spectral linewidth and are inexpensive. The spectrometers constructed with the laser diodes provide det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The extent of interferences from major anions and cations of natural waters and some metal ions were examined by measuring the absorbance of the solution preconcentration step [38]. Cations that may react with IDPI, and anions that may form complexes with the metal ions were studied [39].…”
Section: Effect Of Diverse Ions On the Determinationsmentioning
confidence: 99%
“…The extent of interferences from major anions and cations of natural waters and some metal ions were examined by measuring the absorbance of the solution preconcentration step [38]. Cations that may react with IDPI, and anions that may form complexes with the metal ions were studied [39].…”
Section: Effect Of Diverse Ions On the Determinationsmentioning
confidence: 99%
“…To measure the unstable aqueous components on-site is the best way to avoid possible contamination and chemical alteration of samples. Portable colorimetric spectrophotometers have been developed to satisfy such demand (Nakamoto et al 1997;Soylak et al 1997;Shimazaki et al 1998;Kim et al 2000;Suzuki et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Morin is only weakly fluorescent in nature; however, when chelated with nonparamagnetic metal ions, especially Al 3+ and Be 2+ , it forms highly fluorescent complexes. So, this complexing reagent had been widely used for the fluorimetric determination of Al 3+ and other metal ions [17,18]. It was reported that when morin immobilized on solid support, it exhibited high selectivity for Al 3+ over other cations such as Ca 2+ , Co 2+ , and Pb 2+ [18,19].…”
Section: Introductionmentioning
confidence: 99%